Integrated use of farm manure and synthetic nitrogen fertilizer improves nitrogen use efficiency, yield and grain quality in wheat - Rehim, Abdur; Khan, Maryam; Imran, Muhammad; Bashir, Muhammad Amjad; Ul-Allah, Sami; Khan, Muhammad Naeem; Hussain, Mubshar (Italian Journal of Agronomy, 2020)
Lower nitrogen use efficiency (NUE) is a major yield limiting factor in semi-arid regions due to poor organic contents of the soils. There is a close relationship between soil organic matter and NUE of fertilizers. Therefore, this study was conducted to assess the effect of sole N fertilizer and its combinations with organic amendments (farm manure combinations) on N use efficiency and crop productivity. For this purpose, a two-year field study was conducted to access the influence of integrated use of synthetic N fertilizer (urea) and farm manure on N use efficiency and wheat productivity. Treatments include i.e. Control, 100% N by Urea + 0%N by farm manure (FM), 75% N by Urea + 25 % N by FM, 50% N by Urea + 50% N by FM, 25% N by Urea + 75% N by FM, 0% N by Urea + 100% N by FM arranged in a triplicate randomized complete block design having recommended N rate of 150 kg ha–1. The results revealed that the treatment having 75% Urea and 25% FM followed by 50% Urea and 50% FM showed better results in term of wheat growth and yield. There was 98% increase in N uptake of wheat grains and 200% increase in NUE by the application of 75% urea+25% FM relative to sole application of urea. This study suggests use of 3:1 ratio of urea and FM for maximum NUE and sustainable wheat production.